Small molecule SMU-CX24 targeting toll-like receptor 3 counteracts inflammation: A novel approach to atherosclerosis therapy - Xiaohong Cen; Baoqu Wang; Yuqing Liang; Yanlin Chen; Yu Xiao; Shaohua Du; Kutty Selva Nandakumar; Hang Yin; Shuwen Liu; Kui Cheng (Elsevier, 2022)
Toll-like receptor 3 (TLR3), as an important pattern recognition receptor (PRR), dominates the innate and adaptive immunity regulating many acute and chronic inflammatory diseases. Atherosclerosis is proved as an inflammatory disease, and inflammatory events involved in the entire process of initiation and deterioration. However, the contribution of TLR3 to atherosclerosis remains unclear. Herein, we identified the clinical relevance of TLR3 upregulation and disease processes in human atherosclerosis. Besides, activation of TLR3 also directly led to significant expression of atherogenic chemokines and adhesion molecules. Conversely, silencing TLR3 inhibited the uptake of oxLDL by macrophages and significantly reduced foam cell formation. Given the aberrance in TLR3 functions on atherosclerosis progression, we hypothesized that TLR3 could serve as novel target for clinical atherosclerosis therapy. Therefore, we developed the novel ellipticine derivative SMU-CX24, which specifically inhibited TLR3 (IC50 = 18.87 ± 2.21 nmol/L). In vivo, atherosclerotic burden was alleviated in Western diet fed ApoE−/− mice in response to SMU-CX24 treatment, accompanying notable reductions in TLR3 expression and inflammation infiltration within atherosclerotic lesion. Thus, for the first time, we revealed that pharmacological downregulation of TLR3 with specific inhibitor regenerated inflammatory environment to counteract atherosclerosis progression, thereby proposing a new strategy and probe for atherosclerosis therapy.